Membership dropout rates and associated factors in a community-based health insurance scheme in southern Ethiopia: a mixed method study - Haile, Yosef; Abdulkadir, Hanan; Shewangizaw, Misgun; Meskele, Simeon; Temesgen, Kidus; Haile, Temesgen; Niguse, Daniel; Hailegebreal, Samuel; Biratu, Getahun Gorfu (Frontiers in Health Services, 2023)
Background: Dropout from community-based health insurance (CBHI) membership is a common problem in low-income countries, even if its implementation leads to substantial improvement in the utilization of essential health services. Few studies have addressed the factors contributing to dropout rates in southern Ethiopia. Therefore, the purpose of this study was to determine the rate of CBHI dropout in southern Ethiopia as well as any contributing factors.Methods: This mixed-method cross-sectional study was conducted among 460 randomly selected CBHI-enrolled households at the Arba Minch Health and Demography Surveillance System site from November 1, 2021, to April 30, 2022. The quantitative data were collected by an open data kit (ODK). using an interviewer-based structured questionnaire and analyzed using Statistical Package for the Social Sciences (SPSS) version 25.0. Multivariable logistic regression was applied to identify significant variables. The qualitative data were used to support the quantitative findings and were gathered through in-depth interviews (by the CBHI coordinator and three purposively selected health extension workers) and focus group discussions (in two randomly selected villages). The qualitative data were analyzed using thematic analysis. Finally, triangulation was used to present both the quantitative and qualitative findings. Results: This study found that 92 (21.5%) people stopped their community-based health insurance membership. The presence of sick adults (AOR = 0.281, 95%CI [0.136-0.581]), trust of participants in the contracted health facilities (AOR = 0.227, 95%CI [0.121-0.436]), and poor knowledge of the participants (AOR = 5.518, 95%CI [1.526-19.950]) were significant predictors.The magnitude of the dropout rate was high in this study when compared with the national target. The absence of a sick adult, the absence of trust among participants, and the poor knowledge status of the participants were significant predictors. We suggest that the health facility managers, the CBHI coordinating office, and the district health office give priority to implementing a wide range of knowledge improvement activities and a transparent system in public health facilities. Studies with longitudinal research designs are called for at a wide range of national levels to address the limitations of this study.